Mathematics Learning Innovation: Interactive Learning Videos to Increase Student Learning Activity and Motivation - Awaliyah, Ilka Nur; T, Ahmad Yani (STKIP Singkawang, 2025)
This study aims to explore the effectiveness of using interactive learning videos in increasing students' activeness and motivation in mathematics. Student activeness and motivation are important factors in the teaching and learning process, especially in the context of mathematics education which is often considered challenging. The method used in this study is a literature review, with an analysis of 23 relevant research articles published between 2022 and 2024. The articles obtained were searched on the Google database and used publish or perish. The results of the study indicate that several studies have proven that interactive learning videos can increase student participation in class discussions and collaboration in group activities. Students who use this media feel more involved and enthusiastic in following lessons, which has a positive impact on understanding abstract mathematical concepts. In addition, interesting learning videos can create a fun learning atmosphere, so that students are more motivated to learn. This finding is in line with the opinions of previous researchers who stated that the use of technology in learning can increase student engagement. The main conclusion of this study is that the integration of interactive learning videos is an effective strategy to create a dynamic learning atmosphere and increase student motivation and activeness in learning mathematics. Therefore, it is recommended for educators to apply this method in the learning process in order to achieve better results and meet students' needs in understanding mathematics materials more deeply. Thus, this study provides an important contribution to the development of innovative and relevant learning methods in today's digital era, as well as opening up opportunities for further research on the use of technology in education. Inovasi Pembelajaran Matematika : Video Pembelajaran Interaktif Untuk Meningkatkan Keaktifan dan Motivasi Belajar SiswaABSTRAKPenelitian ini bertujuan untuk mengeksplorasi efektivitas penggunaan video pembelajaran interaktif dalam meningkatkan keaktifan dan motivasi belajar siswa di mata pelajaran matematika. Keaktifan dan motivasi siswa menjadi faktor penting dalam proses belajar mengajar, terutama dalam konteks pendidikan matematika yang sering dianggap menantang. Metode yang digunakan dalam penelitian ini adalah kajian studi literatur, dengan analisis terhadap 23 artikel penelitian yang relevan yang diterbitkan antara tahun 2022 hingga 2024. Artikel yang diperoleh dilakukan pencarian pada google database dan penggunaan publish or perish. Hasil penelitian menunjukkan bahwa beberapa penelitian sudah membuktikan bahwa video pembelajaran interaktif dapat meningkatkan partisipasi siswa dalam diskusi kelas dan kolaborasi dalam kegiatan kelompok. Siswa yang menggunakan media ini merasa lebih terlibat dan bersemangat dalam mengikuti pelajaran, yang berdampak positif pada pemahaman konsep-konsep matematika yang abstrak. Selain itu, video pembelajaran yang menarik dapat menciptakan suasana belajar yang menyenangkan, sehingga siswa lebih termotivasi untuk belajar. Temuan ini sejalan dengan pendapat para peneliti sebelumnya yang menyatakan bahwa penggunaan teknologi dalam pembelajaran dapat meningkatkan keterlibatan siswa. Simpulan utama dari penelitian ini adalah bahwa integrasi video pembelajaran interaktif merupakan strategi yang efektif untuk menciptakan suasana belajar yang dinamis dan meningkatkan motivasi serta keaktifan siswa dalam belajar matematika. Oleh karena itu, disarankan bagi pendidik untuk menerapkan metode ini dalam proses pembelajaran guna mencapai hasil yang lebih baik dan memenuhi kebutuhan siswa dalam memahami materi matematika secara lebih mendalam. Dengan demikian, penelitian ini memberikan kontribusi penting bagi pengembangan metode pembelajaran yang inovatif dan relevan dalam era digital saat ini, serta membuka peluang untuk penelitian lebih lanjut mengenai penggunaan teknologi dalam pendidikan.Kata Kunci : video interaktif; motivasi; keaktifan; inovasi pembelajaran